A nylon 66 composition and preparation method thereof
By modifying nylon 66 resin and combining it with glass fiber, the existing nylon materials have been solved inadequate resistance to alcoholylation and cracking in high temperature and high humidity environments, and the mechanical properties of the materials have been improved and suitable for the manufacturing of automotive radiator parts.
Patent Information
- Application Number
- CN202410195803.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-02-22
AI Technical Summary
In the working environment of automotive radiator water tank components, existing nylon materials are difficult to meet the erosion requirements of ethylene glycol and high-temperature aqueous solutions, and cracking problems are prone to occur.
By modifying the nylon 66 resin with aromatic diamine chain extender and combining it with glass fibers, a modified nylon 66 composition is formed, thereby improving the material's resistance to alcoholylation and cracking.
It significantly improves the alcoholylation and crack resistance of nylon materials, enhances the mechanical properties of the materials, and is suitable for the manufacturing of automotive radiator parts.
Smart Images

Figure BDA0004709610340000061 
Figure BDA0004709610340000071 
Figure BDA0004709610340000072
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a nylon 66 composition and a preparation method thereof. Background Art
[0002] Nylon, also known as polyamide (PA), is a general term for thermoplastic resins containing repeated amide groups (-NHCO-) on the main chain of the molecule, including aliphatic nylon, aromatic nylon, semi-aromatic nylon and new varieties of special nylon. Nylon materials themselves have excellent mechanical properties and are widely used in the automotive industry, especially in the field of radiators. The development and application of high-performance nylon materials have important application value.
[0003] The working environment of automobile radiator water tank components requires that the material be resistant to erosion by ethylene glycol and aqueous solutions above 100°C, and that cracking and other problems are not allowed to occur during assembly and use. However, the impact toughness, dimensional stability and water absorption of existing nylon materials are easily affected by temperature and humidity, making it difficult to meet the functional testing and actual use requirements of the parts. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a nylon 66 composition and a preparation method thereof. The present invention uses a chain extender to modify the nylon 66 resin, effectively improving the alcoholysis resistance and cracking resistance of the nylon material.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] In a first aspect, the present invention provides a nylon 66 composition comprising the following components in parts by weight:
[0007] Modified nylon 66 resin 58-72 parts; glass fiber 23-38 parts; nucleating agent 0.1-0.5 parts; processing aid 0.5-3.5 parts;
[0008] The modified nylon 66 resin is a composite of nylon 66 resin grafted with an aromatic diamine chain extender, wherein the mass ratio of the aromatic diamine chain extender to the nylon 66 resin is (1-4):100; and the average diameter of the glass fiber is 7-10 μm.
[0009] The present invention modifies nylon 66 resin by using a chain extender in a specific proportion, which helps to improve the compatibility between nylon 66 resin and other components, and thus helps to improve the mechanical properties of the material after alcoholysis. In addition, by adding glass fiber and compounding with the modified nylon 66 resin, it is helpful to improve the crack resistance of the material, and at the same time, it is also helpful to further improve the mechanical properties of the material. The inventor speculates that this is because the interface area between the glass fiber and the nylon 66 resin is increased, thereby enhancing the bonding force between the interfaces, and the load on the nylon 66 resin is transferred to the glass fiber, thereby greatly improving the mechanical properties of the material.
[0010] Preferably, the average diameter of the glass fibers is 7-8 μm.
[0011] If the average diameter of the glass fiber is too large, the bonding force between the nylon 66 resin and the glass fiber is affected, and cracks are likely to appear on the surface of the nylon material; if the average diameter of the glass fiber is too small, the glass fiber is likely to agglomerate, resulting in reduced dispersion of the glass fiber, and thus reducing the mechanical properties of the nylon material. Therefore, the present invention controls the average diameter of the glass fiber within the range of 7-8 μm, so that the alcoholysis resistance and cracking resistance of the material are greatly improved.
[0012] Preferably, the aromatic diamine chain extender is at least one of 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 3,5-dimethylthiotoluenediamine (DMTDA), 1,4-bis-sec-butylaminobenzene, and diethyltoluenediamine (DETDA).
[0013] Preferably, the mass ratio of the aromatic diamine chain extender to the nylon 66 resin is in the range of any one of 1:100, 2:100, 3:100, 4:100 or both.
[0014] Preferably, the average diameter of the glass fiber is in the range of any one or both of 7 μm, 8 μm, 9 μm and 10 μm.
[0015] Preferably, the nylon 66 composition comprises the following components in parts by weight:
[0016] 60-70 parts of modified nylon 66 resin; 25-35 parts of glass fiber; 0.1-0.5 parts of nucleating agent; 0.7-3 parts of processing aid.
[0017] Preferably, the mass percentage of the modified nylon 66 resin in the nylon 66 composition is not less than 60%.
[0018] Preferably, the viscosity of the nylon 66 resin is 2.7-2.8.
[0019] The viscosity of the nylon 66 resin in the present invention is tested using the ISO 306 standard, with a temperature of 25° C., a solvent of 96% sulfuric acid, and a solution solubility of 1% g / ml.
[0020] Preferably, the nylon 66 resin has a melt flow rate of 5-15 g / 10 min at 275° C. and a load of 0.325 kg according to ISO 1133-2011.
[0021] Preferably, the nucleating agent is at least one of nano-silica and an ionomer of an EAA copolymer.
[0022] Preferably, the nucleating agent is a mixture of nano-silica and ionomer of EAA copolymer, and the mass ratio of the nano-silica to the ionomer of EAA copolymer is 1:(0.3-4), and more preferably 1:(1-3).
[0023] In the present invention, the ionomer compound of nano-silicon dioxide and EAA copolymer in a specific ratio is used, which is beneficial to accelerate the crystallization of nylon materials, improve the crystallinity of nylon 66 resin, reduce the corrosion effect of solvents on nylon materials during aging, thereby improving the alcoholysis resistance of nylon materials, and at the same time, no cracks are generated on the surface of the nylon material, so that the crack resistance of the nylon material is significantly improved.
[0024] Preferably, the mass ratio of the nano-silica to the ionomer of the EAA copolymer is in the range of any one of 1:1, 1:2, 1:3 or both.
[0025] Preferably, the particle size of the nano-silicon dioxide is 1-100 nm.
[0026] Preferably, the processing aid is at least one of a lubricant, an antioxidant, and a thermal stabilizer.
[0027] Preferably, the nylon 66 composition comprises the following components in parts by weight:
[0028] Lubricant 0.3-1 part; heat stabilizer 0.3-1 part; antioxidant 0.1-0.5 part.
[0029] Preferably, the lubricant is at least one of an ester lubricant, a montanate lubricant, ethylene bisstearamide, and polyethylene wax.
[0030] Preferably, the heat stabilizer is at least one of a copper salt heat stabilizer, potassium bromide, and cuprous iodide.
[0031] Preferably, the antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant.
[0032] More preferably, the antioxidant is a compound of a hindered phenol antioxidant and a phosphite antioxidant, and the mass ratio of the hindered phenol antioxidant to the phosphite antioxidant is (2-5):2.
[0033] In a second aspect, the present invention further provides a method for preparing a nylon 66 composition, comprising the following steps:
[0034] (1) extruding and granulating a chain extender and nylon 66 resin to obtain a modified nylon 66 resin;
[0035] (2) The modified nylon 66 resin is uniformly mixed with other components, melt-extruded and granulated to obtain the nylon 66 composition.
[0036] The method of the invention is simple and convenient to operate and is conducive to industrial production.
[0037] Preferably, the modified PA66 resin in step (1) is obtained by melt extrusion of an aromatic diamine chain extender and nylon 66 resin at 260-280°C.
[0038] Preferably, in step (2), the temperature of the twin-screw extruder is 240-280° C., and the screw speed is 300-400 rpm.
[0039] In a third aspect, the present invention also provides a use of a nylon 66 composition in the preparation of automobile radiator parts.
[0040] The nylon 66 composition prepared by the present invention has excellent alcoholysis resistance and cracking resistance, and can be used to prepare automobile radiator parts. The obtained radiator has the best alcoholysis resistance and cracking resistance at the same time.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The present invention modifies nylon 66 resin by using a chain extender in a specific proportion, which helps to improve the compatibility between nylon 66 resin and other components, and thus helps to improve the mechanical properties of the material after alcoholysis. In addition, by adding glass fiber and compounding with the modified nylon 66 resin, it is helpful to improve the crack resistance of the material, and at the same time, it is also helpful to further improve the mechanical properties of the material. The inventor speculates that this is because the interface area between the glass fiber and the nylon 66 resin is increased, thereby enhancing the bonding force between the interfaces, and the load on the nylon 66 resin is transferred to the glass fiber, thereby greatly improving the mechanical properties of the material. DETAILED DESCRIPTION
[0043] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments, but the protection scope and implementation methods of the present invention are not limited thereto.
[0044] Unless otherwise specified, the materials and reagents used in the following examples are commercially available.
[0045] Examples 1-17
[0046] The embodiments of the nylon 66 composition and the preparation method thereof of the present invention, the components of the nylon 66 composition are shown in Table 1.
[0047] The preparation method of the nylon 66 composition comprises the following steps:
[0048] The modified nylon 66 resin is uniformly mixed with other components, and then added into a twin-screw extruder for melt extrusion and granulation to obtain the nylon 66 composition.
[0049] The temperature of the twin-screw extruder is 240-280° C., and the screw speed is 300-400 rpm.
[0050] Comparative Examples 1-6
[0051] The difference between each comparative example and the embodiment is only in the type and proportion of components, as shown in Table 2.
[0052] Among the components described in each embodiment and comparative example:
[0053] The nylon resin 1 is unmodified nylon 66 resin;
[0054] The nylon resin 2 includes nylon 66 resin and an aromatic diamine chain extender, the mass ratio of the two is 100:0.5, and the aromatic diamine chain extender is 1,4-bis-sec-butylaminobenzene, which comes from Dofuket, and the typical brand is Unilink4100;
[0055] The nylon resin 3 includes nylon 66 resin and an aromatic diamine chain extender, the mass ratio of the two is 100:1, and the aromatic diamine chain extender is 1,4-bis-sec-butylaminobenzene, which comes from Dofuket, and the typical brand is Unilink4100;
[0056] The nylon resin 4 includes nylon 66 resin and an aromatic diamine chain extender, the mass ratio of the two is 100:2, and the aromatic diamine chain extender is 1,4-bis-sec-butylaminobenzene, which comes from Dofuket, and the typical brand is Unilink4100;
[0057] The nylon resin 5 includes nylon 66 resin and an aromatic diamine chain extender, the mass ratio of the two is 100:3, and the aromatic diamine chain extender is 1,4-bis-sec-butylaminobenzene from Dofuket, and the typical brand is Unilink4100;
[0058] The nylon resin 6 includes nylon 66 resin and an aromatic diamine chain extender, the mass ratio of the two is 100:4, and the aromatic diamine chain extender is 1,4-bis-sec-butylaminobenzene, which comes from Dofuket, and the typical brand is Unilink4100;
[0059] The nylon resin 7 includes nylon 66 resin and an aromatic diamine chain extender, the mass ratio of the two is 100:5, and the aromatic diamine chain extender is 1,4-bis-sec-butylaminobenzene from Dofuket, and the typical brand is Unilink4100;
[0060] The nylon resin 8 includes nylon 66 resin and aliphatic amine chain extender, the mass ratio of the two is 100:1, and the aliphatic amine chain extender is Clearlink 8000, which comes from Zhangjiagang Rui Chemical Co., Ltd.;
[0061] The nylon resin 9 includes nylon 66 resin and an aromatic diamine chain extender, the mass ratio of the two is 100:2, and the aromatic diamine chain extender is diethyltoluenediamine, 99% industrial grade, commercially available;
[0062] The nylon resin 10 includes nylon 66 resin and an aromatic diamine chain extender, the mass ratio of the two being 100:2, and the aromatic diamine chain extender is 3,5-dimethylthiotoluenediamine, 99% industrial grade, commercially available;
[0063] The preparation method of the nylon resin 2-10 is as follows: nylon 66 resin and a chain extender are mixed according to a proportion and sent into an extruder for extrusion and granulation to obtain the nylon resin;
[0064] The temperature zone of the extruder is set to a temperature of 260-280° C. and a screw speed of 300-400 rpm.
[0065] The nylon 66 resin is from Jinzhai Hongwei New Materials Co., Ltd., and the typical grade is PA66 HW-01. The nylon resins 1-10 are the same type, and the viscosity of the nylon 66 resin is 2.7-2.8;
[0066] The nylon 66 resin in the nylon resins 1-10 has a melt flow rate of 10 g / 10 min at 275° C. and a load of 0.325 kg according to ISO 1133-2011;
[0067] The glass fiber is from Jushi Group, and the typical grade is E225. The following glass fibers with different diameters are obtained through manual screening:
[0068] The average diameter of glass fiber 1 is 5 μm;
[0069] The average diameter of glass fiber 2 is 7 μm;
[0070] The average diameter of the glass fiber 3 is 10 μm;
[0071] The average diameter of the glass fiber 4 is 12 μm;
[0072] The heat stabilizer is a copper salt heat stabilizer: commercially available;
[0073] The antioxidant is a mixture of a commercially available hindered phenol antioxidant and a commercially available phosphite antioxidant in a ratio of 1:1;
[0074] The lubricant is silicone masterbatch: commercially available;
[0075] The nucleating agent 1 is nano-SiO 2 , brand number 56200, average particle size 50nm, from Huaxia Reagent;
[0076] The nucleating agent 2 is an ionomer of an EAA copolymer: from Honeywell, the typical brand is Aclyn295A;
[0077] Nucleating agent 3 is a Brüggemann nucleating agent, P22.
[0078] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0079] Table 1
[0080]
[0081]
[0082] Table 2
[0083]
[0084]
[0085] In order to verify the performance of the nylon 66 composition of the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:
[0086] 1. Tensile strength: The sample was injection molded into a 170mm*10mm*4mm dumbbell-shaped specimen and tested according to ISO 527-1-2012 method with a tensile rate of 5mm / min;
[0087] 2. Evaluation of alcoholysis resistance: According to the requirements of automobile alcoholysis resistance, the prepared tensile sample is placed in a solution of ethylene glycol and water (the volume ratio of the two is 1:1), and then an alcoholysis resistance aging test is carried out at 135°C and 1008H. After the aging test, the tensile strength of the material is evaluated;
[0088] 3. Evaluation of crack resistance: The material is prepared into a 100*100*2mm square plate, and the prepared sample is placed in a solution of ethylene glycol and water (the volume ratio of the two is 1:1), and then an alcoholysis aging test is carried out at 135°C and 1008H. After the aging test, the crack condition on the surface of the sample is evaluated.
[0089] The surface cracks per unit area are shown below:
[0090] Grade A: no cracks;
[0091] Grade B: There are a few cracks, the number of cracks is less than 5;
[0092] Grade C: There are a large number of cracks, with the number of cracks exceeding 5.
[0093] 4. The alcoholysis resistance retention rate is the rate of change of the tensile strength of the material before and after the alcoholysis experiment, and is calculated as follows: alcoholysis resistance retention rate = [1-(tensile strength of the material before alcoholysis-tensile strength of the material after alcoholysis)] / tensile strength of the material before alcoholysis × 100%.
[0094] The above experimental results are shown in Tables 3 and 4.
[0095] Table 3
[0096]
[0097] Table 4
[0098]
[0099] According to the comparison between Comparative Examples 1-2 and Example 2, if the nylon 66 resin is not modified by a chain extender, the alcoholysis resistance retention rate of the material is much lower than that of Example 2, indicating that after the nylon 66 resin is modified by a chain extender, the alcoholysis resistance of the material is significantly improved. If other chain extenders are used to modify the nylon 66 resin, the effect of the present invention cannot be achieved.
[0100] According to Comparative Examples 3-4, when the mass ratio of the chain extender to the nylon 66 resin is too large or too small, the tensile strength of the material after the alcoholysis test is reduced, and obvious cracks appear on the surface of the material after the alcoholysis aging test, indicating that the chain extender is not modified by any ratio of the nylon 66 resin to achieve the effect of the present invention. Therefore, only when the mass ratio of the chain extender to the nylon 66 resin is (1-4): 100 can the material have both high alcoholysis resistance and cracking resistance. Moreover, according to Comparative Examples 5-6, when the diameter of the glass fiber is too large or too small, after the alcoholysis test, obvious cracks appear on the surface of the material, indicating that the glass fiber is not compounded with the modified nylon 66 resin using any diameter to achieve the effect of the present invention, and the diameter of the glass fiber can only be greatly improved in the range specified by the present invention.
[0101] According to Examples 6-8 in Table 3, the tensile strength of the material after the alcoholysis test is improved, and no cracks appear on the surface of the material after the alcoholysis test, indicating that the present invention adopts a specific ratio of nano-silica and EAA copolymer ionomer compound, which can significantly increase the alcoholysis resistance of the material and greatly improve the crack resistance of the material.
[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A nylon 66 composition, characterized in that: The composition comprises the following components in parts by weight: Modified nylon 66 resin 58-72 parts; glass fiber 23-38 parts; nucleating agent 0.1-0.5 parts; processing aid 0.5-3.5 parts; The modified nylon 66 resin is a composite of nylon 66 resin grafted with an aromatic diamine chain extender; the mass ratio of the aromatic diamine chain extender to the nylon 66 resin is (1-3):100; The average diameter of the glass fiber is 7-10 μm; The aromatic diamine chain extender is at least one of 3,3'-dichloro-4,4'-diaminodiphenylmethane, 3,5-dimethylthiotoluenediamine, and diethyltoluenediamine; The nucleating agent is a mixture of nano-silica and an ionomer of an EAA copolymer.
2. The nylon 66 composition according to claim 1, characterized in that The mass ratio of the nano-silicon dioxide to the EAA copolymer is 1:(0.3-4).
3. The nylon 66 composition according to claim 1, characterized in that The nylon 66 resin has a melt flow rate of 5-15 g / 10 min at 275° C. and a load of 0.325 kg according to ISO 1133-2011.
4. The nylon 66 composition according to claim 1, characterized in that The processing aid is at least one of a lubricant, an antioxidant and a heat stabilizer.
5. The nylon 66 composition according to claim 4, characterized in that At least one of (a) to (c): (a) the lubricant is at least one of an ester lubricant, a montanate lubricant, ethylene bis stearamide, and polyethylene wax; (b) the heat stabilizer is at least one of a copper salt heat stabilizer and potassium bromide; (c) The antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant.
6. The method for preparing the nylon 66 composition according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Extruding and granulating an aromatic diamine chain extender and nylon 66 resin to obtain a modified nylon 66 resin; (2) The modified nylon 66 resin is uniformly mixed with other components, and then added into a twin-screw extruder for melt extrusion and granulation to obtain the nylon 66 composition.
7. The method for preparing a nylon 66 composition according to claim 6, characterized in that: In the step (2), the temperature of the twin-screw extruder is 240-280° C., and the screw speed is 300-400 rpm.
8. Use of the nylon 66 composition according to any one of claims 1 to 5 in the preparation of automobile radiator parts.
Citation Information
Patent Citations
Composite material for recycling waste vehicle nylon products and preparation method thereof
CN101792596A
Hydrolysis-resistant alcoholysis-resistant nylon 66 composite material and preparation method thereof
CN102516761A